Menyeimbangkan IQ, EQ, SQ Dalam Pendidikan Berwajah Insani - Mansur - (Millah: Journal of Religious Studies, 2005)
Education is as one a way bequeathed a value, which can become guidance to face our life and also it can improve our fate and human civilization. To face globalization era should be strove education which has the ability to develop intellectual intelligence, emotional intelligence and spiritual intelligence. Therefore, education is not only developing intellectual intelligence, which gives negative effect but also it is not able to solve the human problem in globalization era. If we see the phenomena that many destructions hempen in this world because of the model of education which based on intellectual intelligence and be oriented toward materialistic. That is why education model needs to make balancing intellectual intelligence, emotional intelligence and spiritual intelligence. So education which is needed by human being is intellectual intelligence, emotional intelligence and spiritual intelligence as a unit in improving human quality.